Bridging the gap between self‐assessment and faculty assessment of clinical performance in restorative dentistry: A prospective pilot study - Ghaith Alfakhry; Khattab Mustafa; M. Abdulhadi Alagha; Hussam Milly; Mayssoon Dashash; Issam Jamous (Wiley, 2022)
Abstract Purpose/Objectives The current study was undertaken to investigate whether self‐assessment of clinical skills of undergraduate dental students could be bridged with faculty assessment by deliberate training over an extended period. A secondary aim was to explore students' perception of self‐assessment and its effect on their learning and motivation. Material and Methods A prospective pilot study was conducted at the Department of Restorative Dentistry at Damascus University. Sixteen students participated in the study, ranging in age between 22 and 23 years. A modified Direct Observation of Procedural Skills form with a grading rubric was used to register and guide students' self‐assessment; both were pretested on four students before the study. In total, four clinical encounters were completed by each student. Students were trained on how to conduct proper self‐assessment before and after each clinical encounter. A postcourse questionnaire was used to investigate students' perception of self‐assessment. Results Bias in self‐assessment decreased consistently after each encounter, and the difference in bias between the first (bias = 0.77) and the last encounter (bias = 0.21) was significant with a medium effect size (p = .022, d = 0.64). The percentage of disconfirming performance dimensions decreased from 39.7% to 26.9%. Students' ability to exactly pinpoint strengths improved consistently and significantly. However, their ability to pinpoint areas of improvement was volatile and showed no significant difference. Bland-Altman graph plots showed higher levels of agreement between self‐assessment and faculty assessment. Moreover, students' perception of self‐assessment was very positive overall. Conclusions These findings suggest the possibility that the gap between self‐assessment and faculty assessment could be bridged through deliberate training. Future longitudinal research using a larger sample size is still required to further explore whether self‐assessment can be actively bridged with faculty assessment by deliberate training.